Edukasi Pemanfaatan Jahe Merah Pada Penyakit Infeksi Saluran Pernafasan Akut (Ispa) - Anggraini, Novita; Maharani, Sri Pamilia; Novitri, Dewi Caya; Saputra, Fery Surahman (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Acute Respiratory Tract Infection (ARI) is an infectious disease that can affect the human respiratory system. ARI is an infection of the upper respiratory tract caused by microorganisms, including the nasal cavity, pharynx, and larynx, which lack gas exchange (Mustafa et al., 2023). An estimated 13 million people die from ARI. The disease burden varies widely, ranging from approximately 4 million of the 13 million people in India (48%), Indonesia (38%), Ethiopia (4.4%), Pakistan (4.3%), China (3.5%), Sudan (1.5%), and Nepal (0.3%). New ARIs occur in almost every region of the world. In 2022, Southeast Asia had the highest number of ARI cases worldwide. Approximately 30 countries contributed to the number of cases. (WHO, 2022) The incidence of acute respiratory infections (ARI) in Indonesia is relatively high, reaching 166,702 in 2022. This figure reaches 53% of the 50% target. Of this 53%, 31.4% of ARTI cases occur in toddlers. ARI is the second leading cause of death in children under five (12-59 months), accounting for 9.4%. This disease is an acute respiratory infection with symptoms of fever, cough lasting less than two weeks, runny nose/nasal congestion, and/or sore throat (Ministry of Health, 2022). In addition to medical treatment, ARTI treatment can also be supported by the use of natural ingredients. The combination of ginger and honey has been shown to have a synergistic effect in relieving ARTI symptoms. Red ginger (Zingiber officinale var. rubrum) is a herbal plant long known and used by Indonesians as a traditional medicine. Red ginger contains active compounds such as gingerol, shogaol, and zingerone, which have anti-inflammatory, antioxidant, and antimicrobial properties. These ingredients are useful in helping relieve symptoms of ARI, such as reducing inflammation in the respiratory tract, relieving coughs, and increasing the body's immune system.